Searching for viral antibodies and genome in intraocular fluids of patients with Fuchs uveitis and non-infectious uveitis - Cimino, Luca; Aldigeri, Raffaella; Parmeggiani, Maria; Belloni, Lucia; Zotti, Carlo Alberto; Fontana, Luigi; Invernizzi, Alessandro; Salvarani, Carlo; Cappuccini, Luca (Graefe's archive for clinical and experimental ophthalmology, 2013)
Background To characterise the polyspecific intraocular antibody synthesis in aqueous humor of patients with Fuchs uveitis and other types of non-infectious uveitis. Methods Aqueous and serum samples collected from 24 patients with Fuchs uveitis, 21 patients with non-infectious uveitis, and 27 healthy subjects undergoing elective cataract surgery (control group) were analysed. In addition, vitreous samples, collected from seven uveitis patients (five Fuchs and two panuveitis) during retinal surgery, were examined. Specific immunoglobulin G antibodies against cytomegalovirus (CMV), rubella virus, herpes simplex virus (HSV), and varicella zoster virus (VZV) were investigated, and Goldmann–Witmer coefficients (GWCs) were calculated. Real-time PCR was performed to detect viral genome for HSV, VZV, and CMV, while nested PCR was conducted to detect rubella RNA. Results None of the control samples tested positive for any of the viral antibodies investigated. Intraocular antibody production was found in eight samples of patients affected by Fuchs uveitis (6/8 positive for rubella virus and 2/8 positive for herpes virus). Among patients with non-infectious uveitis, three tested positive for intraocular antibody production (one RV, one HSV and one for VZV). PCR was positive for RV in two patients with Fuchs uveitis, in three patients with non-infectious uveitis (one for RV and two for HSV), and in three control subjects (one for CMV and one for HSV). Conclusions Our series confirmed the presence of specific viral antibodies, especially against rubella virus, in the subgroup of patients affected by Fuchs uveitis, suggesting that this virus may be responsible for this chronic inflammatory condition. Rubella virus is probably the main causative agent of Fuchs uveitis, but other viruses may also be involved in the pathogenesis of this disease.